Non-employee individual taxpayer compliance - Aqmarina Vaharani Paramaduhita; Elia Mustikasari (Emerald Publishing Limited, 2018)
The purpose of this paper is to determine what factors may affect taxpayer (TP) compliance.This research uses five independent variables such as income, TP’s perception on tax penalties, law and enforcement, fair tax treatment and the use of tax money in a transparent and accountable way. The dependent variable is the compliance of individual TPs non-employees. The data used are primary data obtained from questionnaires on KPP Surabaya Rungkut and processed using a multiple linear regression method with SPSS 21.0 Software for Windows.The results show that partially income does not affect the compliance of individual TP non-employees; however, four other independent variables on the TP’s perception of penalties, law enforcement, tax treatment and the use of tax money simultaneously had a positive effect.All independent variables had a positive effect on compliance by individual TP non-employees on KPP Surabaya Rungkut.